Identification and characterization of novel QTL conferring internal detoxification of aluminium in soybean. (24th April 2021) - Li, Yang; Ye, Heng; Song, Li; Vuong, Tri D; Song, Qijian; Zhao, Lijuan; Shannon, J Grover; Li, Yan; Nguyen, Henry T
Abstract : Novel QTL associated with aluminum tolerance were identified from a soybean recombinant inbred line population and confirmed in near-isogenic backgrounds, conferring internal detoxification for aluminum toxicity instead of Al 3+ exclusion. Abstract: Aluminium (Al) toxicity inhibits soybean root growth, leading to insufficient water and nutrient uptake. Two soybean lines ('Magellan' and PI 567731) were identified differing in Al tolerance, as determined by primary root length ratio, total root length ratio, and root tip number ratio under Al stress. Serious root necrosis was observed in PI 567731, but not in Magellan under Al stress. An F8 recombinant inbred line population derived from a cross between Magellan and PI 567731 was used to map the quantitative trait loci (QTL) for Al tolerance. Three QTL on chromosomes 3, 13, and 20, with tolerant alleles from Magellan, were identified. qAl_Gm13 and qAl_Gm20 explained large phenotypic variations (13–27%) and helped maintain root elongation and initiation under Al stress. In addition, qAl_Gm13 and qAl_Gm20 were confirmed in near-isogenic backgrounds and were identified to epistatically regulate Al tolerance via internal detoxification instead of Al 3+ exclusion. Phylogenetic and pedigree analysis identified the tolerant alleles of both loci derived from the US ancestral line, A.K.[FC30761], originally from China. Our results provide novel genetic resources for breeding Al-tolerant soybean and suggest that internal detoxification contributes to soybean tolerance to excessive soil Al.